Implementation of the Authority of the Village Consultative Body in Supervising the Village Budget According to Law Number 6 of 2014 in Mburukulu Village, Pahunga Lodu District, East Sumba Regency - Dairo, Ambrosius Frader; Umbu Lily Pekuwali; Norani Asnawi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study uses an empirical juridical research method with sources. So the data collection techniques used: 1. Interviews are data collection by means of direct questions and answers to information using a list of questions as interview guidelines related to the topic of this study. 2. Document/literature studies are library research conducted by collecting documents in the form of books, legislation, journals and other written materials related to the research topic. The results and conclusions, the implementation of the authority of the village deliberative body in Mburukulu Village, Pahunga Lodu District, East Sumba Regency, did not run smoothly when viewed from the involvement and activeness of members of the Village Deliberative Body both in supervising the implementation of government in managing village finances and organizing village government. And the inhibiting factors in the implementation of the authority of the Village Deliberative Body are: a. human resources, b. infrastructure, c. interaction between members of the Village Deliberative Body, village officials, and the village community, d. understanding of the functions and authorities as members of the Village Deliberative Body, e. economy